Analysis of Activity Programs in Achieving Key Performance Indicators (IKU) in the 2020 LLDIKTI Region II Performance Agreement (PK) - Alwi Alwi (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to determine the policies implemented by the LLDIKTI Wilayah II in achieving the Main Performance Indicators (IKU). This type of research is descriptive qualitative with data collection methods carried out by interviews with decision-making officials who are very influential in determining the Main Performance Indicators for the 2020 fiscal year. The results of this study indicate that LLDIKTI Wilayah II has made every effort so that the activities carried out can reach the IKU. targeted in the 2020 Performance Agreement. From this research it is known that LLDIKTI Wilayah II has seven Main Performance Indicators (IKU) and carries out eleven activities to achieve IKU.